2023
DOI: 10.1029/2023wr034848
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations and Yields of Mercury, Methylmercury, and Dissolved Organic Carbon From Contrasting Catchments in the Discontinuous Permafrost Region, Western Canada

L. M. Thompson,
M. Low,
R. Shewan
et al.

Abstract: Climate change and permafrost thaw may impact the mobilization of terrestrial dissolved organic carbon (DOC), mercury (Hg), and neurotoxic methylmercury (MeHg) into aquatic ecosystems; thus, understanding processes that control analyte export in northern catchments is needed. We monitored water chemistry for 3 years (2019–2021) at a peatland catchment (Scotty Creek) and a mixed catchment (Smith Creek) in the Dehcho (Northwest Territories), within the discontinuous permafrost zone of boreal western Canada. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 103 publications
(161 reference statements)
0
0
1
Order By: Relevance
“…Only one research site (Site 10), which was an active peat extraction site, showed a similar trend, with significantly increasing DOC concentrations from August to October. In a study conducted in Canada, Thompson et al [55] estimated slightly lower runoff, 80-213 to 164-236 mm y −1 , respectively, compared to our estimations, where the annual runoff varied from 307 mm in silver birch forests to 423 mm in active and abandoned peat extraction sites without vegetation.…”
Section: Doc Concentrations and Affecting Factorscontrasting
confidence: 82%
“…Only one research site (Site 10), which was an active peat extraction site, showed a similar trend, with significantly increasing DOC concentrations from August to October. In a study conducted in Canada, Thompson et al [55] estimated slightly lower runoff, 80-213 to 164-236 mm y −1 , respectively, compared to our estimations, where the annual runoff varied from 307 mm in silver birch forests to 423 mm in active and abandoned peat extraction sites without vegetation.…”
Section: Doc Concentrations and Affecting Factorscontrasting
confidence: 82%